Exploring the Interaction of Cinema and City through Technology: The Case of Cinemapp in Valladolid - Rincón-Borrego, Iván; Alonso-García, Eusebio; Perez-Barreiro, Sara (SAUC - Street Art and Urban Creativity (repository), 2024)
This study examines the interplay between cinema, architecture, and emerging technology, focusing on the web application Cinemapp.net and its impact on the city of Valladolid. The application enables users to explore the cinematic ecosystem and architectural heritage of Valladolid, facilitating an interactive approach to experiencing the city’s rich cinematic history and architectural legacy. We analyze how digital technologies, such as augmented reality and graph-databases, reconfigure urban experiences and the perception of cinematic spaces. The social and urban impact of Cinemapp is assessed in terms of its contribution to the public perception of Valladolid and its influence on tourism and urban planning. Additionally, this work explores how Cinemapp serves as a digital historical archive, preserving and documenting the cinematic and architectural heritage of Valladolid, underscoring the importance of digital platforms in cultural heritage conservation. Our analysis suggests that the integration of digital technologies into the cinematic representation of cities not only alters the aesthetic and cultural experience of urban space but also provides new tools for urban regeneration and cultural tourism, creating a living archive that evolves alongside the city.